The Effect of Audit Committee Characteristics on Audit Report Lag (Study on Consumer Cyclicals Companies Listed on IDX, 2020–2022) - Rahim, Khyra (Tax Accounting Applied Journal, 2024)
This study aims to examine the effect of audit committee characteristics on Audit Report Lag in manufacturing companies, particularly in the Consumer Cyclicals sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2022. The characteristics observed include audit committee competence, the number of audit committee members, audit committee meeting frequency, independence, and gender. Using agency theory as the theoretical foundation, this research argues that an effective audit committee can reduce information asymmetry and agency costs, thus accelerating audit completion. The sample was selected using purposive sampling, and panel data regression analysis was employed to test the hypotheses. Classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation were also conducted. The results show that only the number of audit committee members has a significant negative effect on Audit Report Lag. Meanwhile, competence, meeting frequency, independence, and gender do not show significant influence. These findings emphasize the importance of audit committee structure in improving audit timeliness, supporting the implementation of good corporate governance.